2007
DOI: 10.1111/j.1462-2920.2007.01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of true‐branching cyanobacteria from geothermal sites and hot springs of Costa Rica

Abstract: Costa Rica is at the centre of the Mesoamerican biodiversity hotspot. Little is known about cyanobacteria from this region so far. Here, four isolates of the order Stigonematales (section V) were characterized in a polyphasic approach. All strains were isolated from geothermal sites and hot springs of Costa Rica. However, one of them, identified as Westiellopsis sp. Ar73, did not grow at more than 40 degrees C. Based on its identical 16S rRNA to several previously isolated Westiellopsis sp. and Fischerella mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 63 publications
3
54
0
Order By: Relevance
“…Cyanobacteria have been identified in other thermal microbial mats included members of the unicellular Synechococcales (mainly the genus Synechococcus) (Sompong et al, 2005;Steunou et al, 2006Steunou et al, , 2008 and the filamentous Stigonematales (genera Fischerella and Mastigocladus) (Miller et al, 2006;Lacap et al, 2007Lacap et al, , 2007Finsinger et al, 2008). The dominating cyanobacterial phylotypes discovered in the microbial mats of the Porcelana hot spring corroborated these data, with the exception of the unicellular cyanobacteria.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Cyanobacteria have been identified in other thermal microbial mats included members of the unicellular Synechococcales (mainly the genus Synechococcus) (Sompong et al, 2005;Steunou et al, 2006Steunou et al, , 2008 and the filamentous Stigonematales (genera Fischerella and Mastigocladus) (Miller et al, 2006;Lacap et al, 2007Lacap et al, , 2007Finsinger et al, 2008). The dominating cyanobacterial phylotypes discovered in the microbial mats of the Porcelana hot spring corroborated these data, with the exception of the unicellular cyanobacteria.…”
Section: Discussionmentioning
confidence: 53%
“…Within the cyanobacteria, unicellular members such as Synechococcus and Cyanothece typically dominate at temperatures above 60°C (Ward et al, 1998;Ward and Castenholz, 2000;Papke et al, 2003;Steunou et al, 2006Steunou et al, , 2008. At lower temperatures (~60-40°C), filamentous, non-heterocystous genera such as Phormidium and Oscillatoria and heterocystous genera such as Calothrix, Fischerella and Mastigocladus are common (Sompong et al, 2005;Miller et al, 2006;Finsinger et al, 2008;Coman et al, 2013). Although heterocystous cyanobacteria are richly represented in many hot springs with a neutral pH, their role and capacity as providers of fixed nitrogen is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. S1 shows the amino acid sequences of the HetR proteins from several cyanobacterial species including Anabaena (6), Nostoc punctiforme (12), Fischerella MV11 (13), and Trichodesmium erythraeum (11). Fischerella grows at elevated temperatures, up to 60°C (13), so we thought that its HetR might provide better crystals for structure determination.…”
Section: Resultsmentioning
confidence: 99%
“…Also, MILLER et al (2009) found sympatric diversification along a temperature gradient (39-54°C) as a potent source of evolution, in White Creek, Yellowstone N.P. Geographic isolation may be an important aspect of cyanophycean evolution, including Mastigocladus, studied in Costa Rica, (FINSINGER et al 2008). CASTENHOLZ (1972) forecasted the existence of the two genetic types in Mastigocladus in his paper about Surtsey Island.…”
Section: Notesmentioning
confidence: 99%